Wage growth and the measurement of social security's financial condition - Jagadeesh Gokhale (Levy Economics Institute of Bard College, 2006)
Government spending on the elderly is projected to increase rapidly as the American population becomes older. As a result, many policymakers and budget analysts are concerned about the continued viability of entitlement programs such as Social Security. The Social Security trustees' economic growth projections receive considerable attention because many people believe that higher growth would significantly improve the program's actuarial balance (that is, reduce its actuarial deficit). This belief is validated by Social Security trustees' calculations that show larger 75-year actuarial balances under faster assumed real wage growth rates. Since 2003 the trustees have reported the program's actuarial balance measured in perpetuity. But they do not provide sensitivity analysis that examines the impact of various assumptions on the infinite-term actuarial balance. This paper shows analytically that faster wage growth may reduce Social Security's infinite-term actuarial balance if the ratio of workers to retirees continues to decline rapidly beyond the 75th year. This result holds even if the decline in that ratio ceases after just two decades beyond the 75th year. The paper reports stylized calculations of the impact of real wage growth and demographic changeincluding time-varying rates of change based on official projections for the U.S. economyon Social Security's actuarial balance in a multi-period setting. Finally, the Social Security and Accounts Simulator (SSASIM) actuarial model of Social Security financing is used to estimate the degree to which increased wage growth could negatively affect the system's infinite-term actuarial balance. These results raise questions about the conventional wisdom that holds that improved wage growth would affect Social Security's financing, and how a widely used measure of Social Security's financing captures those effects.
Keywords: H55; E62; 330; Social Security; wage growth; demographic change; infinite horizon; actuarial balance; sustainability